Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Sepeda Motor di Tunas Honda Kota Bima - Agus Maulana; Sri Ernawati; Ita Purnama (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the influence of the marketing mix on motorcycle purchasing decisions at PT. Tunas Honda Kota Bima. The marketing mix variables examined in this research consist of product, price, place, and promotion. The study employs an explanatory research design with a quantitative approach. Data were collected using questionnaires distributed to 50 respondents who had previously purchased motorcycles at PT. Tunas Honda Kota Bima, selected through a purposive sampling technique. Data analysis was conducted using simple linear regression with SPSS version 22. The findings indicate that the marketing mix has a positive and significant effect on purchasing decisions, as evidenced by the regression coefficient value of 0.452 and a significance level of p = 0.001. The coefficient of determination (R²) of 19.3% implies that the marketing mix contributes to purchasing decisions, while the remaining 80.7% is influenced by other factors such as brand image and customer reviews. These results highlight the importance of an integrated marketing strategy focusing on improving product quality, setting competitive prices, implementing effective promotions, and optimizing distribution channels to enhance consumer purchasing decisions.